Integrasi Panel Surya untuk Mendukung Sistem Hidroponik dan Aquaponik Berkelanjutan di Lingkungan Pendidikan: Pendekatan Praktis di SDI As-Salam dan SMPIT As-Salam, Malang - Setyarini, Putu Hadi; Fajriani, Sisca; Nurwati, Tri; Roviq, Mochammad; Inayati, Dian (Unri Conference Series: Community Engagement, 2024)
The technical advice initiative for the implementation of solar panels in hydroponic and aquaponic culture at SDI As-Salam and SMPIT As-Salam in Malang City seeks to enhance the efficiency and sustainability of the school's hydroponic and aquaponic systems. The primary issues encountered are elevated operational expenses related to power and reliance on PLN. The team executed a solution by installing solar panels with a cumulative capacity of 800 watts peak, including four 200-watt panels and an energy storage battery with a 400-watt capacity. The training results indicated that the solar panels could power the hydroponic gadget continuously for 24 hours. The training included the principal and instructors, who then instructed pupils in hydroponic and aquaponic farming techniques. Success indicators encompass the enhancement of skills and knowledge among educators and pupils pertaining to renewable energy technologies and agricultural practices, the effective installation and functioning of solar panels, and the diminishment of reliance on PLN electricity. This activity offers real advantages through reduced operational expenses while also enhancing students' understanding of environmentally focused technologies. Additional potential prospects encompass the commercialization of hydroponic vegetable production and project-based teaching aimed at enhancing environmental consciousness.